Critical perspectives on leadership emotion, toxicity, and dysfunction - edited by Jeanette Lemmergaard (Northampton Edward Elgar Pub, 2013)
This book offers a critique of the field of leadership studies, focusing on the dynamics between post-heroic leadership and the notion of functional and dysfunctional emotions.
Keywords: Leadership